Pengembangan Handout berbasis E-learning untuk Meningkatkan Literasi Visual Siswa tentang Paruh Burung Finch - Andi Gafur, Irfan; Prayogo; Tika Nabila Sholihan (Lembaga Anotero Scientific Pekanbaru, 2024)
The objective of this research is to develop alternative learning materials in the form of handouts, aimed at enhancing interactivity and fostering sustained student engagement throughout the learning process. By addressing the imperative requirement for enhanced learning resources to augment student comprehension, this study endeavors to supplant conventional, uninspiring teaching methodologies with innovative alternatives. Utilizing the Research and Development (R&D) approach within the framework of the ADDIE model, students were the principal subjects of inquiry. Furthermore, this study substantiates the credibility of the developed handouts, with a coefficient value surpassing 0.8, thereby affirming their validity and reliability for educational implementation